Decreased Lead Levels, Kupang, and Boiling - Juniawanti, Dwy Retno; Mindiharto, sestiono (Journal of Public Health Science Research (JPHSR), 2020)
Lead is one of the very dangerous heavy metals that can pollute the environment. Sidoarjo Regency is an industrial area in East Java which has several factories, some of which do not process industrial waste properly. This untreated waste is made directly into the water so that it pollutes the water so that it serves the biota in the water, one of which is mussel. This research aims to determine the effect of boiling in an effort to reduce lead levels in Kupang. This research was conducted by taking samples of Kupang in Balongdowo village, Candi Sidoarjo District. This research was included in an experiment to reduce mercury content with boiling time of 15 minutes, 30 minutes, 45 minutes and 60 minutes. The analyzed results are presented in tabular and graphical form. The results showed a decrease in lead levels at a boiling time of 30 minutes by 0.8886 mg / L with the difference reaching a decrease of 0.211 and a boiling time of 45 minutes can decrease by 0, 8211 mg / L with a difference of a decrease of 0.0675. This means that there is an effect of boiling in an effort to reduce lead levels in Kupang.